Optimización del proceso productivo a través de un estudio de tiempos y movimientos en la fabricación de bloques en la parroquia Eloy Alfaro, en el barrio la Calera - Almagro Ortiz, Diego Hernán (2019)
In the present investigation a study of times and movements in the manufacturing process of artisan blocks was carried out in order to optimize the production process of it. For which the inspection and evaluation of the block manufacturing process was planned, analyzing, the importance, the purpose, the purpose and the beneficiaries that are the handcrafted block manufacturers of the Eloy Alfaro parish. In the neighborhood La Calera is known for the production of handcrafted blocks, so after carrying out a current study of movement times in one of ours it was identified that an average cycle time of these processes is therefore 207.4 hours a correct standardization and strategies of the processes were applied, which allowed to reduce the time of the activities by 1.93% (207.9h).This proposal avoids workers the physical wear and tear by transcorting material with long runs and several unnecessary activities. This study allows to obtain a reduction of the time and movements used in the elaboration of the blocks, which can be a permanent reference and an effective tool in the manufacturing process of improving the products of the Eloy Alfaro blockhouses. For this study to have good results, the blockers must redesign the distribution of the plant and a constant training program for the personnel of the production area that allows them to use the best form of the resources.